Intramuscular lipoma of the mental region: A report of a rare case - Akio Shibata; Kou Kawahara; Takashi Oguri; Kazeto Takao (Elsevier, 2021)
Intramuscular lipoma in the mental region is rare with this being, to our knowledge, only the third reported case. It was difficult to differentiate between intramuscular lipoma and well-differentiated liposarcoma by clinical and radiological findings in this case, and we performed excisional biopsy with adequate margins. A V-Y subcutaneous tissue pedicle island advancement flap was used to reconstruct the cutaneous defects. Because the ability of infiltrating lipoma to infiltrate the adjacent muscles and recur locally may lead to a false clinical diagnosis such as liposarcoma, it is essential that histopathologic examination is performed.